2004
DOI: 10.1016/j.ntt.2003.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Lead (Pb2+) modulation of potassium currents of guinea pig outer hair cells

Abstract: Outer hair cells (OHC) are mechanosensitive sensory cells of the inner ear cochlea and are involved in modulating the activity of inner hair cells in the transduction of an acoustic stimulus. Potassium (K + ) currents play an important role in the sensory transduction process. K + currents were recorded from acutely dissociated OHC obtained from the guinea pig organ of Corti. The whole-cell patch clamp technique was employed. We identified a channel that exhibited outward current of the delayed rectifier type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…This result suggests that Pb 2+ blocks Cav1.2 channels, and, at higher doses, possibly K + channels as well. These results are consistent with previous reports using other cell types, and can explain the toxic actions of lead (Atchison 2003;Liang et al 2004;Madeja et al , 1997;Peng et al 2002;Yu et al 2003).…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result suggests that Pb 2+ blocks Cav1.2 channels, and, at higher doses, possibly K + channels as well. These results are consistent with previous reports using other cell types, and can explain the toxic actions of lead (Atchison 2003;Liang et al 2004;Madeja et al , 1997;Peng et al 2002;Yu et al 2003).…”
Section: Introductionsupporting
confidence: 93%
“…Lead ions have also been reported to reversibly inhibit delayed and transient outward potassium currents in hippocampal neurons (Madeja et al 1995(Madeja et al , 1997Yu et al 2003). These effects were found in both steady-state activation and inactivation experiments (Madeja et al 1997;Yu et al 2003); however, similar findings were not observed in Kv channels from outer hair cells (Liang et al 2004). In addition to the NMDA receptor, acute lead exposure has been reported to modify the action of other receptors by modifying their function and also reducing their expression levels during chronic exposures (Marchetti 2014;Vijverberg et al 1994b).…”
Section: Introductionmentioning
confidence: 97%
“…Other animal studies also found no significant Pb-related effects on the cochlea. Experimental studies using guinea pigs exposed to Pb, or in vitro experiments on dissociated guinea pig outer hair cells bathed in Pb acetate found no apparent morphological changes in the cochlea, no marked effects on the endocochlear potential or the cochlear microphonic response, and no significant effects on outer hair cell electromotility (the process leading to the generation of otoacoustic emissions) (Gozdzik-Zolnierkiewicz & Moszynski, 1969; Yamamura, et al, 1989; Tuncel, et al, 2002; Liang et al, 2004). Because the cochlear microphonic response (or receptor potential) is generated primarily by the outer hair cells of the inner ear, ototoxic effects should be manifested in both a diminished cochlear microphonic response and abnormal DPOAE, although DPOAE may be more hair cell place-specific than the cochlear microphonic.…”
Section: Discussionmentioning
confidence: 97%
“…Pb 2ϩ blocks voltage-gated Ca 2ϩ and K ϩ channels and hyperpolarization-activated channels but activates SK4, a Ca 2ϩ -activated K ϩ channel, by acting as a Ca 2ϩ surrogate. These findings suggest that Pb 2ϩ acts differently on different ion channels (Cao and Houamed, 1999;Atchison, 2003;Dai et al, 2003;Liang et al, 2004). Therefore, its effects may differ between different types of two-pore K ϩ channels.…”
Section: Enhancement Of Human Trek-2 Currents By Zinc 623mentioning
confidence: 90%